The association between systolic blood pressure reduction during clonidine suppression testing and the decrease in plasma catecholamines and metanephrines. Issue 10 (3rd September 2020) - Golani, Tiran; Fishman, Boris; Sharabi, Yehonatan; Olswang‐Kutz, Yael; Leibowitz, Avshalom; Grossman, Ehud; Shlomai, Gadi
Abstract: Borderline isolated norepinephrine (NE) and normetanephrine (NMT) elevation is common among patients with suspected pheochromocytoma and paraganglioma (PPGL). The clonidine suppression test (CST) may help establish the etiology in these cases. Prolonged laboratory processing and/or paucity of reliable biochemical assays may limit the utility of CST. The aim of this study was to evaluate whether blood pressure (BP) reduction during CST is associated with alterations in plasma NMT/NE, thereby potentially providing an immediate indication of CST results. In this cross‐sectional study, the authors included all consecutive patients with suspected PPGL who underwent CST from January 1, 2014, to December 31, 2019. Linear regression models were conducted to evaluate the association between BP reduction and decrease in plasma NMT/NE. The final analysis included 36 patients (17 males). The decrease in systolic BP (SBP) 90 minutes postclonidine was associated with a decrease in plasma NMT (R = 0.668, P  = .025) and NE (R = 0.562, P  = .005). A 40% decrease in NMT and NE correlated with a 9.74% and 7.16% decrease in SBP, respectively. Subgroup analyses demonstrated that the association between SBP reduction and the decrease in plasma NMT (R = 0.764, P  = .046) and NE (R = 0.714, P  = .003) strengthens among patients with hypertension and among those with diabetes mellitus (R = 0.974, P  = .026 for NMT). In conclusion, SBP reduction during CST is associated with plasma NMT and NE decrease. Therefore, the decrease in SBP 90 minutes postclonidine may serve as an immediate complementary clinical tool for PPGL diagnosis.